Corruption: how should Christians respond? - P. M. Theron; G. A. Lotter (Acta Theologica)
The results of the 2010 Corruption Perceptions Index of Transparency International indicate the seriousness of the worldwide corruption problem. Although recent decades have witnessed a global public awareness and an increase in attempts to eradicate corruption, it is an ongoing problem. It is evident that legislation is not an effective deterrent and it should therefore also be tackled at grass roots level by involving ordinary citizens, including Christians. On an individual level, it entails personal honesty and the living of exemplary lives. The golden rule of Jesus Christ can serve as a guiding principle for everyday life, namely do to others what you would have them do to you. On the public level, it requires the willingness to act as whistle-blowers. Christians are called and sanctioned by God to participate actively in society’s transformation. They need to think ethically and to act with the proper attitude.